2009
DOI: 10.1007/s11892-009-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel antigens in type 1 diabetes: The importance of ZnT8

Abstract: The presence of circulating islet cell autoantibodies distinguishes type 1A diabetes (T1D) from other diabetic syndromes and determination of autoantigen genes and proteins is instrumental in understanding T1D as a clinical entity and in investigating the pathogenesis of the disease. ZnT8 was recently defined as a candidate autoantigen based on a -bioinformatics analysis focused on discovery of beta-cell-specific proteins associated with the regulatory pathway of secretion. The native molecule does not lend it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 52 publications
(39 reference statements)
3
51
0
Order By: Relevance
“…87% of the patients had at least one diabetes Ab detected. ZnT8 Ab positivity was the highest (72%) in children with short disease duration ( < 5 years) and this is consistent with the prevalence (60%-80%) reported in previous studies [3,[20][21][22][23]. IA-2 Ab positivity was the lowest irrespective of diabetes duration, the age at onset or patient age at the time of testing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…87% of the patients had at least one diabetes Ab detected. ZnT8 Ab positivity was the highest (72%) in children with short disease duration ( < 5 years) and this is consistent with the prevalence (60%-80%) reported in previous studies [3,[20][21][22][23]. IA-2 Ab positivity was the lowest irrespective of diabetes duration, the age at onset or patient age at the time of testing.…”
Section: Discussionsupporting
confidence: 90%
“…Autoantibodies (Ab) to islet cell antigens such as glutamic acid decarboxylase (GAD), insulinoma antigen 2 (IA-2), insulin and the more recently identified zinc transporter 8 (ZnT8) [3] are serological markers of T1DM. Measurement of these specific Ab has an important role in clinical practice including classification of diabetes, identification of individuals at risk of developing T1DM and as endpoints in observation studies [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently defined as a major target of humoral autoimmunity in human T1D based on a bioinformatics analysis (Dang et al, 2011;Wenzlau et al, 2009). Autoantibodies to ZnT8 (ZnT8A) have been therefore detected in high prevalence in newly diagnosed type 1 diabetic patients (Yang et al, 2010) and obviously overlap with GADA, IA2A, and IAA (Wenzlau et al, 2007).…”
Section: Zinc Transporter 8 Autoantibodiesmentioning
confidence: 99%
“…Among them, ZnT8 was observed to be one of the major autoantigens and a predictive marker in risk groups before onset of the disease. Wenzlau et al followed the individuals from birth to T1D onset and they found that ZnT8 antibodies (ZnT8A) appeared as early as 2 years of age and showed increasing levels and prevalence persisting to disease onset (Wenzlau et al, 2009;Wenzlau et al, 2007). Some suggested a strong inverse relationship between the age of T1D onset and the prevalence of ZnT8A (Kawasaki, 2012).…”
Section: Introductionmentioning
confidence: 99%